Relationship between professional self-concept and perceived organizational support with family functioning in nurses in Isfahan, Iran - Leila Sahraian; Mousa Alavi; Fatemeh Ghaedi-Heidari (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Vocational issues affect nurses' family functioning in long term. So the purpose of this study is to investigate the relationship between professional self-concept and perceived organizational support with nurses' family functioning. MATERIALS AND METHODS: This descriptive correlational study conducted in hospitals affiliated to Isfahan University of Medical Sciences and 250 nurses who met the inclusion criteria participated in this study. The samples were selected conveniently from December 2022 to August 2022. To collect data, Cowin's professional self-concept questionnaire, Eisenberger's perceived organizational support questionnaire, and Epstein's family function measurement were used. Data collection was done in one step and cross-sectional. Descriptive statistics and inferential methods of data analysis consisted of Pearson's correlation coefficient and multiple linear regression were used. Data were analyzed with statistical package for the social sciences (SPSS) version 22. RESULTS: One of the six dimensions of professional self-concept consisted of staff relations significantly predicted the family function of nurses (P = .004). No significant relationship was found between perceived organizational support and nurses' family function (P = .825). CONCLUSION: Promoting the healthcare organizations' human climate may improve nurses' wellbeing and hereby their family functioning which could further improve quality of healthcare services. It may be worthwhile to suggest supporting interpersonal and interprofessional relationships to ensure a healthy professional life for the nurses.